Comparing the Effects of Vivid Writing and Photographs on Moral Judgment in Public Relations. - McEntee, Rebecca S.; Coleman, Renita; Yaschur, Carolyn (Journalism & Mass Communication Quarterly)
This experiment explores whether vivid writing can improve ethical reasoning by testing it in public relations against non-vivid writing, alone and in combination with pictures. Vivid writing has effects similar to photographs on attention, memory, emotion, and persuasion; this study explores whether vivid writing effects includes one of the more important effects that photographs can have—improving ethical reasoning. Results show non-vivid writing alone raised participants’ moral judgment, however photographs increased participants’ perceptions of the issues as morally important. Vivid writing did increase participants’ empathy, and empathy was related to support for the organization. Photographs increased participants’ perception of the issue as morally important.